2006
DOI: 10.1108/02640470610714224
|View full text |Cite
|
Sign up to set email alerts
|

Internet use by the faculty members of Kuwait University

Abstract: Purpose-This study is designed to investigate the patterns of internet use by the faculty including purposes for use, its impact on teaching and research, internet resources that they use, and the problems faced while using the internet. Design/methodology/approach-A questionnaire, expert-reviewed and pilot-tested, was used to collect data from the faculty coming from four colleges of Kuwait University, i.e. Arts, Social Sciences, Sciences, and Engineering. Half of the 491 potential participants were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 11 publications
(19 reference statements)
2
40
2
3
Order By: Relevance
“…Despite the fact that devices such as cell phones might divert students' attention, yet, no one can deny their importance as high-tech educational tools. Beyond no doubt, acquiring a foreign or a second language attracts the interest of educationalist worldwide (Kukulska-Hulme, 2009;Cavus & Ibrahim, 2009;Al-Ansari, 2006). For example, acquiring lexical items, and developing listening skills in Korea (Nah et al, 2008) are crucial when learning a foreign or a second language.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that devices such as cell phones might divert students' attention, yet, no one can deny their importance as high-tech educational tools. Beyond no doubt, acquiring a foreign or a second language attracts the interest of educationalist worldwide (Kukulska-Hulme, 2009;Cavus & Ibrahim, 2009;Al-Ansari, 2006). For example, acquiring lexical items, and developing listening skills in Korea (Nah et al, 2008) are crucial when learning a foreign or a second language.…”
Section: Introductionmentioning
confidence: 99%
“…The author did not rate the level of utilisation as done by the researcher and bulletin board service was not used by Lecturers' for their academic activities in the universities studied. As noted by Al-ansari (2006) the level of Internet services and resources utilisation varies from individual to individual, institution to institution and country to country. The study further revealed that Internet services and resources were used for the purposes of communication, research, publication, finding of current information and cooperation with colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of skill and lack of English language proficiency were the most commonly reported barriers that prevented respondents from using the internet effectively. It is certain, however, that internet usage has increased in developing Arab countries, with a multi-disciplinary study undertaken at Kuwait University (Al-Ansari, 2006) reporting internet use by 89 percent of respondents.…”
Section: Review Of the Literaturementioning
confidence: 94%